Prevalência da infecção pelo HPV e de alterações citológicas anais e cervicais em transgêneros atendidos em ambulatório especializado no Espírito Santo entre 2018 a 2021 - Costa, Franco Luís Salume (2022)
Introduction: Transgenderism is considered a health’s social determinant for the transgender population. There are access barriers to health services and demographic censuses that makes unfeasible the determination of sexually transmitted infections (STIs) prevalence. It is known that there is an increased risk of acquiring STIs due to risky sexual behavior. HPV infection is the most common STI among adults and data about its prevalence in transgender people is scarce and necessary. Objectives: To determine the prevalence of HPV infection in the transgender population treated at a specialized service at the University Hospital of Espírito Santo and its association with cytological changes. Materials and Methods: This is a cross-section carried out from August 2018 to May 2021, including 110 transgender users. Data collection consisted of survey, search for HPV, chlamydia, gonorrhea, trichomoniasis in samples from anal and cervical region and oncotic cytology survey and blood samples’ screening for HIV, syphilis, hepatitis B and C. Data were stored and processed using SPSS–data entry (Statistical Package for the Social Sciences), 20. Results: Transgender men represented 60.9% of the sample (n = 67), while transgender women were 34.5% (n = 38). The mean age was 27.7 years, with a standard deviation of 9.131. The prevalence of HPV was 58.3%, with 50% among transgender men and 81.25% among transgender women. By anogenital site, positive HPV in the cervical region were 38% and, in the anal region, 25% in transgender men. Transgender women were HPV positive in the anal region 48.1%. Anal cytology was altered in 23.5% of the transgender women, and the cervical cytology among 9.5% in men. Syphilis, trichomoniasis, HIV, genital wart, herpes, chlamydia, and hepatitis B, were found in, respectively, 13.6%, 12.5%, 5.5%, 4.5%, 4.5%, 4.1% e 0.9%. Conclusion: Prevalence studies of HPV, STIs and their clinical-behavioral correlation are still needed to provide comprehensive, inclusive and respectful care to this population. STI and neoplasm screening and prevention policies should be prioritized.